2001
DOI: 10.1016/s0955-0674(00)00251-9
|View full text |Cite
|
Sign up to set email alerts
|

Anoikis mechanisms

Abstract: Anoikis is defined as apoptosis that is induced by inadequate or inappropriate cell-matrix interactions. It is involved in a wide diversity of tissue-homeostatic, developmental and oncogenic processes. The central problem of anoikis is to understand how integrin-mediated cell adhesion signals control the apoptotic machinery. In particular, the initiation of the caspase cascade in anoikis remains to be explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
1,027
0
28

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,259 publications
(1,075 citation statements)
references
References 69 publications
20
1,027
0
28
Order By: Relevance
“…Growing evidence indicates that collaborative pathways derived from these two signals are crucial in regulating a range of cell activities, such as proliferation, differentiation, apoptosis, adhesion, and migration [93][94][95][96].…”
Section: Versican Interaction With Epidermal Growth Factor Receptor (mentioning
confidence: 99%
“…Growing evidence indicates that collaborative pathways derived from these two signals are crucial in regulating a range of cell activities, such as proliferation, differentiation, apoptosis, adhesion, and migration [93][94][95][96].…”
Section: Versican Interaction With Epidermal Growth Factor Receptor (mentioning
confidence: 99%
“…Taken together, these results strongly suggest that FZD10 overexpression induces Rac1 and JNK activation through phosphorylation of Dvl2 and Dvl3 proteins. Furthermore, as the Rac1 activation was indicated to be important for the inhibition of detachment-induced cell death (anoikis) (Frisch and Screaton, 2001;Cheng et al, 2004), we investigated the effect of FZD10 on anchorage-independent cell growth. When the cells were cultured in soft agar, the numbers of colonies in 1273/99-FZD10-1 and 1273/99-FZD10-2 were increased up to two-fold in comparison with the parental 1273/99 cells or those transfected with mock control (Mock1) (Figure 3g).…”
Section: Disruption Of Actin Cytoskeleton By Fzd10 Overexpressionmentioning
confidence: 99%
“…Normal mammary epithelial cells require attachment to the ECM to inhibit anoikis, which is defined as caspase-dependent cell death caused by ECM detachment. 17 It has become clear that tumor progression and metastasis require cancer cells to inhibit anoikis, oftentimes through alterations in intracellular signaling pathways. [18][19][20] Interestingly, previous studies have shown that ErbB2 and EGFR, which are hyperactivated in a substantial percentage of IBC patients, 21 can effectively antagonize the anoikis program to facilitate anchorage-independent growth.…”
mentioning
confidence: 99%